Aryl diazonium modification on graphite electrode in microbial fuel cell: a review - Muhammad Farhan Hil Me,; Mimi Hani Abu Bakar,; Hazlinda Kamarudin, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Usage of graphite electrode in a microbial fuel cell (MFC) is favored due to their electron conductivity and stability as a base material for the electrode. Also, graphite is favored as it allows the growth of biofilm, which can enhance the cell’s performance. The efficiency is reported improved through modification. Aryl diazonium modification has been reported to induce biofilm formation on the electrode faster. The modification can be done spontaneously or through electrografting of aryl diazonium salt onto the electrode surface. Control over the quantity of grafted aryl diazonium is essential. A thick layer will cause the performance of the system to drop, which may impede the electron transfer from biofilm to the electrode. Aryl diazonium is preferred as it allows a robust biofilm formation when used as a surface modification on the graphite electrode. Modification using aryl diazonium allows the electrode to be more accommodative for biofilm growth, which will increase the performance of the system. However, it does not act as a redox mediator for the system. It has been reported that power density obtained using aryl diazonium modified electrode is 250 mW.m-2, higher than unmodified graphite electrode of 125 mW.m-2. However, not all bacterial species is compatible with aryl diazonium modification. The unmodified graphite biocathode allows a higher power density compared to aryl diazonium modified biocathode. Hence, depending on the quality of aryl diazonium modification and the types of inoculum used, MFC performance can be further maximized.